1992
DOI: 10.1109/20.179409
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between noise-after-write and magnetization dynamics in thin film heads

Abstract: Correlation between noise-after-write and magnetization dynamics i n 30-turn electroplated thin film heads has been investigated by utilising two complementary magneto-optic Kerr effect domain imaging systems and a Barkhausen noise tester. It has been found that heads containing spike-like domains near the backgap closure have significantly higher noise-after-write rates than heads with normal closure domain configurations. A longitudinal 180° wall in the direction of flux conduction at the sloped region of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Various aspects studied include the introduction of trailing shields, [13][14][15] the writer geometry, [16][17][18] and pole-tip geometry. [24][25][26] In our work we have studied the reversal behavior of various patterned permalloy shapes comprising a large element in contact with a small element that to an extent can be likened to the pole tip within the write head. They found that the tapered-neck pole achieved much larger write fields and field gradients than those without a tapered neck.…”
Section: Introductionmentioning
confidence: 99%
“…Various aspects studied include the introduction of trailing shields, [13][14][15] the writer geometry, [16][17][18] and pole-tip geometry. [24][25][26] In our work we have studied the reversal behavior of various patterned permalloy shapes comprising a large element in contact with a small element that to an extent can be likened to the pole tip within the write head. They found that the tapered-neck pole achieved much larger write fields and field gradients than those without a tapered neck.…”
Section: Introductionmentioning
confidence: 99%